Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1152/ajplung.1998.275.3.l551
|View full text |Cite
|
Sign up to set email alerts
|

Activation of MAPKs in human bronchial epithelial cells exposed to metals

Abstract: We have previously shown that in vitro exposure to metallic compounds enhances expression of interleukin (IL)-6, IL-8, and tumor necrosis factor-α in human bronchial epithelial cells. To characterize signaling pathways involved in metal-induced expression of inflammatory mediators and to identify metals that activate them, we studied the effects of As, Cr, Cu, Fe, Ni, V, and Zn on the mitogen-activated protein kinases (MAPK) extracellular receptor kinase (ERK), c-Jun NH2-terminal kinase (JNK), and P38 in BEAS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
168
2
9

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(201 citation statements)
references
References 61 publications
15
168
2
9
Order By: Relevance
“…We also find evidence that the intracellular signaling cascades activated by DTDP appear to be similar to those observed by other researchers after exposure to extracellular zinc. Samet et al (1998) reported p38 and ERK activation in human bronchial cells after zinc exposure. Although we observed increases in both ERK and p38 after DTDP treatment, only p38 activation contributes significantly to the observed neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…We also find evidence that the intracellular signaling cascades activated by DTDP appear to be similar to those observed by other researchers after exposure to extracellular zinc. Samet et al (1998) reported p38 and ERK activation in human bronchial cells after zinc exposure. Although we observed increases in both ERK and p38 after DTDP treatment, only p38 activation contributes significantly to the observed neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…MKP5 has been shown to be able to deactivate all MAPK members, with some selectivity for the JNK/SAPK members [63,64]. Cr-induced activation of ERK, JNK and p38 pathways has been shown in a number of different cell lines, while the activation pattern is dependent on the dose/duration of the exposure [57,[65][66][67]. It has been suggested that Cr(VI) can potentially activate inhibitory MKPs [66].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in Flt3, including internal tandem duplication, occur in the juxtamembrane domain at which arsenite trioxide is the most potent signal transducer (40,41). Flt3 internal tandem duplication is a prevalent mutation in various signaling pathways including the MAPK/extracellular signal-regulated kinase (ERK) pathway (18). However, to the best of our knowledge, the role of Flt3 in phospho-receptor tyrosine kinase pathway has not been documented in other systems.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that arsenite can induce reactive oxygen species production and cause DNA damage (13)(14)(15)(16). It may also interfere with the DNA repair system or DNA methylation state, induce inhibition of p53, increase cell proliferation, and alter signal transduction pathways that lead to the activation of transcription factors (17)(18)(19)(20). However, knowledge on the exact carcinogenic mechanism and valid model systems for this compound is still lacking, which creates even more concern for adverse potential of this important environmental pollutant (21).…”
Section: Introductionmentioning
confidence: 99%